2020
DOI: 10.3389/fmicb.2020.00073
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio parahaemolyticus Infection in Mice Reduces Protective Gut Microbiota, Augmenting Disease Pathways

Abstract: Vibrio parahaemolyticus (Vp), a major food-borne pathogen, is responsible for severe infections such as gastroenteritis and septicemia, which may be accompanied by lifethreatening complications. While studies have evaluated factors that affect the virulence of the pathogen, none have investigated the interaction of Vp with gut microbiota. To address this knowledge gap, we compared the effect of Vp on gut bacterial community structure, immunity, liver and kidney function, in pseudo germ-free (PGF) mice and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 85 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…This result suggests that larval survival could be predicted by the abundance of some key genera, rather than the modification of microbial diversity. Several authors show that infections can induce disturbances in the composition of commensal microbiota such as overgrowth of some microorganisms and reduction of others ( Khan and Chousalkar, 2020 ; Vakili et al, 2020 ; Wang et al, 2020 ). For example, V. anguillarum affected the relative abundance of 18 OTUs (Operational Taxonomic Units) and altered alpha and beta diversity ( Nie et al, 2017 ) in ayu ( Plecoglossus altivelis ).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that larval survival could be predicted by the abundance of some key genera, rather than the modification of microbial diversity. Several authors show that infections can induce disturbances in the composition of commensal microbiota such as overgrowth of some microorganisms and reduction of others ( Khan and Chousalkar, 2020 ; Vakili et al, 2020 ; Wang et al, 2020 ). For example, V. anguillarum affected the relative abundance of 18 OTUs (Operational Taxonomic Units) and altered alpha and beta diversity ( Nie et al, 2017 ) in ayu ( Plecoglossus altivelis ).…”
Section: Discussionmentioning
confidence: 99%
“…Factors that affect microbiota composition often have a strong effect and produce changes in composition that can be detected at the phylum level. For example, dietary changes ( 27 , 28 ) and colonization with diverse microbes (e.g., Cryptosporidium parvum [ 29 ], Vibrio parahaemolyticus [ 30 ], and Klebsiella pneumoniae [ 31 ]) produce phylum-level changes. In contrast, the compositions of uncolonized and C. albicans -colonized mice under the conditions of our experiments showed minimal differences at the phylum level ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Species with differential abundance between groups were identified based on LDA scores greater than 3.6. 11 The abundance of species in the phylum Bacteroidetes and the genus Bacteroides were enriched in the control group but not in the other groups. Due to the Vp infection, the gut microflora abundance of the phylum Proteobacteria, the genera Enterobacter, and Prevotella were enriched in the Vp group.…”
Section: P Pentococcus Zy-b Alleviated V Parahaemolyticusmentioning
confidence: 87%
“…9,10 A previous study of ours showed that a lack of intestinal microbial protection signals promotes Vpinduced bleeding and fluid accumulation in the ileum, triggering a pro-inflammatory cascade in the intestinal lamina propria. 11 Thus, there are inextricable links between the Vp infection and intestinal microecology. We believe that promoting a healthy gut microbial community could be an effective treatment strategy for Vp infection.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation